Penerapan Neo Vernakular Simalungun pada Pusat Perbelanjaan di Pematangsiantar - Ramadhan, Indra Sakti; Moerni, Saufa Yardha (Jurnal Ilmiah Teknik Sipil dan Arsitektur (JITAS), 2025)
This study aims to analyze the application of Neo Vernacular Simalungun in shopping centers in PematangSiantar. The problem is focused on the need for a shopping center that is complete with modern facilities and typical of the region. In order to approach this problem, the theoretical reference of Neo Vernacular architecture is used as the basis for design. The data were collected through literature study and qualitative analysis of the Neo Vernacular design principles of Simalungun. This study concludes that shopping centers in Pematangsiantar are designed as modern facilities with the application of the Neo Vernacular Simalungun theme. The building mass is in the middle of the site with circulation surrounding it, equipped with vegetation for aesthetics, air insulation, and noise. Key amenities include elevators, escalators, supermarkets, cinemas, restaurants, and an outdoor park with a sports area and children's playground. The zoning of buildings is divided into public, semi-public, private, and service, with the orientation facing northeast. The application of Simalungun ornaments such as Pinar Gatip-Gatip and the shape of the roof of the Bolon Traditional House strengthens the cultural identity.